Comparative Analysis of Columns Ratio on Structural Performance and Cost Efficiency - Wibowo, Kevin Aprilio; Widjajakusuma, Jack (Jurnal Teknik, 2025)
Planning is crucial in construction as it can significantly reduce costs by aligning structural design with requirements while minimizing excess. This study evaluates the structural performance of columns with different shapes and dimensions, utilizing data from the construction site and Indonesian National Standards (SNI). The analysis reveals that square-shaped columns, with a cross-section ratio close to 1, require less material than rectangular columns, with a 17.35% lower concrete volume and a 23.37% smaller formwork area. However, the reinforcement needed for square columns is 6.38% higher. Overall, square columns lead to a 15.42% reduction in production costs. This also results in lower cement consumption, contributing to decreased CO₂ emissions—Design B using 856.32 kg (18.52%) less cement than Design A. The results support the principles of the Sustainable Development Goals (SDGs), particularly SDG 9 (Industry, Innovation, and Infrastructure), SDG 11 (Sustainable Cities and Communities), SDG 12 (Responsible Consumption and Production), and SDG 13 (Climate Action). These findings align with the Sustainable Development Goals (SDGs), emphasizing the importance of sustainability alongside cost efficiency in structural planning.